SHARPIN regulates collagen architecture and ductal outgrowth in the developing mouse mammary gland. (14th December 2016) - Peuhu, Emilia; Kaukonen, Riina; Lerche, Martina; Saari, Markku; Guzmán, Camilo; Rantakari, Pia; De Franceschi, Nicola; Wärri, Anni; Georgiadou, Maria; Jacquemet, Guillaume; Mattila, Elina; Virtakoivu, Reetta; et al.
Abstract: SHARPIN is a widely expressed multifunctional protein implicated in cancer, inflammation, linear ubiquitination and integrin activity inhibition; however, its contribution to epithelial homeostasis remains poorly understood. Here, we examined the role of SHARPIN in mammary gland development, a process strongly regulated by epithelial–stromal interactions. Mice lacking SHARPIN expression in all cells ( Sharpin cpdm ), and mice with a stromal ( S100a4‐Cre ) deletion of Sharpin, have reduced mammary ductal outgrowth during puberty. In contrast, Sharpin cpdm mammary epithelial cells transplanted in vivo into wild‐type stroma, fully repopulate the mammary gland fat pad, undergo unperturbed ductal outgrowth and terminal differentiation. Thus, SHARPIN is required in mammary gland stroma during development. Accordingly, stroma adjacent to invading mammary ducts of Sharpin cpdm mice displayed reduced collagen arrangement and extracellular matrix (ECM) stiffness. Moreover, Sharpin cpdm mammary gland stromal fibroblasts demonstrated defects in collagen fibre assembly, collagen contraction and degradation in vitro . Together, these data imply that SHARPIN regulates the normal invasive mammary gland branching morphogenesis in an epithelial cell extrinsic manner by controlling the organisation of the stromal ECM. Synopsis: SHARPIN is implicated in regulation of extracellular matrix adhesion molecules. New data show that SHARPIN modulates stromal collagen architecture and matrix turnover in mammary gland fibroblasts during puberty and thereby regulates the outgrowth of mammary ducts. Mice lacking SHARPIN expression ( Sharpin cpdm ) have reduced mammary ductal outgrowth during puberty. Transplantation studies and conditional knockouts show that stromal, and not epithelial, SHARPIN regulates mammary gland development. Collagen bundling and extracellular matrix stiffness are reduced in the Sharpin cpdm mammary gland stroma. Mammary gland fibroblasts that lack SHARPIN demonstrate defective collagen remodelling and turnover in vitro . Abstract : Adhesion regulator SHARPIN modulates stromal collagen architecture and matrix turnover in mammary gland fibroblasts during puberty and thereby regulates the outgrowth of mammary ducts.